Anticancer potential of coumarins from the Ferulago genus - Mansour Mofasseri; Elham Eini; Saber Mofasseri; Bahram Hanifehpour; Fatemeh Zanbili; Ahmad Poursattar Marjani (Results in Chemistry)
Cancer treatment needs better therapeutic agents with fewer side effects compared to the present anticancer and antitumor drugs. Possessing a wide range of chemicals, natural products are considered rich sources of bioactive compounds in treating a broad scope of diseases, especially cancer. Harness the power of coumarins, a natural compound that has shown remarkable efficacy in treating many cancers. This study was aimed to highlight the most promising coumarins from Ferulago genus, their mechanisms of action, and potential therapeutic applications in cancer treatment. In this regard, a broad literature study was conducted applying a considerable number of scientific databases, including Science Direct, Scopus, Web of Science, PubMed, Google Scholar, and EBSCO, to review the latest studies on the anticancer potential of Ferulago genus. The search was limited to studies published up to June 2024. In this review, a collection of diverse reports on Ferulago species with cytotoxic and anticancer activities, as well as isolated coumarins from this genus with anticancer potentials, are presented. The results showed that the Ferulago genus, an extensive reservoir of coumarins, is a promising source for discovering, improving, and designing groundbreaking anticancer and cytotoxic therapeutics. Accordingly, continued investigations into their pharmacological properties and therapeutic applications will be crucial in developing novel anticancer therapies, ultimately contributing to improved patient quality of life.